“Ubicomp” In Software Engineering Applications - Claudia CARSTEA; Ovidiu PASCUTOIU (Communications of International Proceedings, 2021)
Ubiquitous computing (or “ubicomp”) represents a concept increasingly used in software engineering, in which the calculus is made to appear anytime and anywhere. Haptic technology will change our lifestyle and the way how we will interact with fixed or mobile systems in the future. These technologies will be implemented on devices that will act as an extension of our body, of the environment in which we operate. We will be able to control the world around us? Certainly yes. Context-aware was born as a term in the “ubiquitous computing”, or the so-called ubiquitous calculation, which sought to address environmental change with computer systems, which are actually analyzed and designed both statically and dynamically. All over the world, engineers are now working to recreate realistic tactile sensations, for video games and more. Involving contact in human-computer interactions would enhance robotic control, physical rehabilitation, education, navigation, and even communication.
Keywords: Ubicomp; Context-Aware; Control; Interaction